2001
DOI: 10.1590/s0100-204x2001000500012
|View full text |Cite
|
Sign up to set email alerts
|

Composição corporal e exigências nutricionais de cálcio e fósforo de cordeiros Santa Inês em crescimento

Abstract: Dois experimentos foram conduzidos com o objetivo de determinar a composição corporal e estimar as exigências de Ca e P, para ganho em peso, de cordeiros Santa Inês em crescimento. Em cada experimento foram usados 18 animais com 25 a 35 kg de peso vivo (PV), no primeiro, e com 15 a 25 kg no segundo experimento. Seis animais foram abatidos no início de cada experimento para avaliar o conteúdo de Ca e P corporal, servindo como animais referência para o método do abate comparativo, seis animais receberam alimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 11 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…Therefore, reductions in the concentrations of Ca, P and Mg can be attributed to reductions in the proportion of bone tissue in the body of the animal, rather than increased fat deposition. Pérez et al (2001), who studied Santa Inês hair lambs with weights that ranged between 25 and 35 kg of BW, showed that Ca and P values needed for daily gains of 100 to 300 g ranged from 1.63 to 3.48 g Ca and from 0.58 to 1.74 g P. These values were higher than net requirements of the Santa Inês animals determined in this research, and provides evidence that variability can be observed with respect to the nutritional requirements of similar animals. According to Assis et al (2018), estimates of the net Ca and P requirements of several studies conducted in Brazil also showed differences that were up to 100% of the values proposed by the AFRC (1991).…”
Section: Net Requirements For Macrominerals Of Hair Lambsmentioning
confidence: 99%
“…Therefore, reductions in the concentrations of Ca, P and Mg can be attributed to reductions in the proportion of bone tissue in the body of the animal, rather than increased fat deposition. Pérez et al (2001), who studied Santa Inês hair lambs with weights that ranged between 25 and 35 kg of BW, showed that Ca and P values needed for daily gains of 100 to 300 g ranged from 1.63 to 3.48 g Ca and from 0.58 to 1.74 g P. These values were higher than net requirements of the Santa Inês animals determined in this research, and provides evidence that variability can be observed with respect to the nutritional requirements of similar animals. According to Assis et al (2018), estimates of the net Ca and P requirements of several studies conducted in Brazil also showed differences that were up to 100% of the values proposed by the AFRC (1991).…”
Section: Net Requirements For Macrominerals Of Hair Lambsmentioning
confidence: 99%